Low field MR imaging of sellar and parasellar lesions: Experience in a developing country hospital (2011)
Background: Magnetic resonance imaging (MRI), an advancement which followed computed tomography (CT) is expensive and inaccessible in most dveloping countries. However it is the procedure of choice in evaluating sellar and parasellar lessions. Its major advantages are its superior soft tissue contrast differentiation, its capacity for multiplanar imaging and nonexistence of ionising radiation. Its use is relatively new in Nigeria, a developing economy in Africa. Since its introduction in 2005, it has been utilised extensively for neuroimaging at the University College Hospital (UCH), Ibadan; a large hospital is south-western Nigeria. Objective: To review the role and pattern of low field MR imaging in sellar and parasellar lesions presenting to a tertiary care centre in Nigeria. Methods: All 62 patients with clinically suspected sellar and parasellar masses, referred to the department of Radiology, UCH Ibadan for MRI between December 2006 and January 2010 were retrospectively analysed. The examinations were performed using an open 0.2T permanent magnet MR unit. T1W, T2W,T2/ FLAIR, TOF and T1W post gadolinium DTPA sequences of the sellar region were obtained. Result: Of the 62 patients, there were 27 males and 35 females. The modal age group was 40-49 years with a mean age of 39.94 years (±16.65years). Twenty-four cases (38.7%) had histological daignosis, of which 20(83.3%) were consitent with initial MRI diagnosis. Pituitary adenomas were the commonest (58.06%) lesions of the sellar and parasellar regions. Others include parasellar meningiomas, cranipharyngiomas, and gaint aneurysms. Headache and visual impariment were the major presenting features and showed no significant correlation with tumor size. Conclusion: The use of low filed MRI in the diagnostic evalauation of patients with suspected sellar or parasellar lesions in developing countries of low economic resource is commendable as it provides beneficial outcomes in management.